In humans, the flow of business processes: an aesthetic perspective using business process patterns - Monika Blattmeier (Swiss Journal of Business)
“Life is form, and form is the modality of life,” declared the art historian H. Focillon, celebrating the various forms in our universe. This conceptual article explores business process patterns that are perceived, analyzed, and visualized as whole entities or Gestalten. Sensually understanding business processes – specifically, the collective routines, the implicit knowledge that is expressed therein, and, lastly, their uniqueness – is the objective of aesthetic analysis. Aesthetic business processes are determined by individuals that attribute significant value to the work practices and their outputs. This analytical perspective emphasizes the human factor, the unusual, and the power of imagination in light of the numerous transformations, particularly in matters of sustainability, which also present challenges for business process management. A multimodal repertoire that provides texts and images for aesthetic perception is being developed through the use of a pattern format. To figure out the inherent quality of a business process pattern, one must engage with both the problem-solution scheme and its dynamic characteristics inside the process flow. The article illustrates how a specific business process pattern was visualized in collaboration with companies so that aesthetic experiences are also possible during the reception of the visualizations. The value of business process patterns is realized when the dynamics of the process flow are recognized, which establishes the link between what is happening in the process and the process structure, time and space, and knowledge of various domains, thereby encouraging innovative thinking.